High-Risk, but Hidden: Binge Drinking among Men Who Have Sex with Men and Transgender Women in Lima, Peru, 2012-2014 - Passaro, R. Colby (2020)
Background: Binge drinking (BD) is common in Peru, but may not be routinely detected by standard assessments of hazardous drinking. Objectives: We describe prevalence and risk behaviors of men who have sex with men (MSM) and transgender women (TW) in Peru who met criteria for BD as compared with those who met criteria for hazardous drinking. Methods: In a cross-sectional sample of MSM and TW from Lima (2012-2014), we calculated prevalence of BD (consuming ≥6 alcoholic drinks per occasion by AUDIT-3 criteria), conducted bivariate analyses of associations of BD with demographic and behavioral characteristics, and compared prevalence and behaviors of BD to those of hazardous drinkers (identified by AUDIT-10 criteria). Results: Of 1,520 MSM (n = 1,384) and TW (n = 137) with median age 27 years, 74.4% of MSM and 86.9% of TW met criteria for BD. Among MSM, BD was associated with a greater likelihood of using alcohol (41.6% vs. 13.8%; p <.01) or drugs (7.8% vs. 2.8%; p <.01) prior to a recent sexual contact. Among TW, BD was associated with greater frequency of alcohol use (44.9% vs. 11.1%; p <.01) or unprotected anal intercourse (58.8% vs. 33.3%; p =.04) during ≥1 of their three most recent sexual contacts. There was a higher prevalence of BD (75.5%) than hazardous drinking (53.2%) in our sample, with binge drinkers exhibiting similar sexual risk behaviors to hazardous drinkers. Conclusions: Binge drinking is common among MSM and TW in Lima, associated with risky sexual behavior, and may not be adequately captured by AUDIT-10 criteria.